Repositioning Administrative Sanctions for Deforestation due to Nickel Downstream Industry in Indonesia and Nigeria - Daffa Ladro Kusworo; Abdulrazaq Owolabi Abdulkadir (Journal of Judicial Review, 2025)
Industrial downstreaming in the nickel sector is currently a national priority scale that is being intensively carried out by the government since 2020. The projection of processing by the state is intended as the main raw material in the manufacture of battery production as a renewable energy that is environmentally friendly. Unfortunately, uncontrolled damage is also exacerbated by the Job Creation Law which does not provide a clear picture of how administrative sanctions can realize environmental compliance, so that in fact to this day the downstream nickel industry is carried out recklessly. This research uses normative legal methods that refer to laws and regulations related to the environment with the nature of descriptive and explanatory research to analyze the phenomenon of forest destruction in Maluku and Sulawesi. The research is accompanied by literature studies in the form of books, journals, and other literature. Data analysis uses descriptive qualitative to describe ongoing legal phenomena through comparative studies of other countries. The reason for choosing this research is because the crucial nature of forest destruction that has led to environmental deforestation in Halmahera needs to be addressed immediately by examining the legal normativeness in the Job Creation Law and comparing it with the legal phenomenon in Nigeria. This research study also uses a comparative method to find legal symptoms and phenomena that occur in society, especially in other countries.The results show that downstream industries that have an impact on forest destruction, especially deforestation, require repositioning of the administrative sanctions reviewed which were removed in the Job Creation Law. The repositioning is constructed by the author as an effort to aggravate administrative sanctions without ignoring the concept of reparatoir in it like the Nigerian state, so that administrative sanctions still embody environmental ethical values through the assessment of violations that prioritize the concept of real forest restoration.